Detox - Paul, Gill, 1960- (London Collins, 2007)
Alcohol, cigarettes, caffeine, sugar, salt, as well as pollution inside and out are all toxins and can wear your body down after a while. This guide explains the science behind detoxing and how to achieve a successful detox. It includes topics such as: your body's natural detox system; principles of detox diets; preparing for detox; and more.
Include Index, Glossary and Illustration
Keywords: Detoxification (Health) -- Detoxification (Health)